A comparative assessment of service quality perspectives and satisfaction in ports: evidence from Nigeria. (8th April 2009) - Ugboma, Chinonye; Ugboma, Ogochukwu; Damachi, Bona
The study presents the findings on the effect of service quality on port users' satisfaction from two distinct methodological perspectives. The study utilised a sample of Nigerian shippers wherein service quality is operational via two distinct measures – SERVQUAL and technical/functional quality. These two service quality measures are compared and contrasted as to their ability in predicting port users' satisfaction in Nigerian ports. To assess the validity of these findings, two moderators of the service-quality/port user's satisfaction relationship are introduced and evaluated. Finally, we examined the potential utility of employing separate measures for port users' satisfaction from the perspectives of both technical and functional aspects of the service delivery process. Overall, our findings are of importance to port managers as they strive to identify efficient and effective approaches for improving quality.